2011
DOI: 10.1007/s12034-011-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on microstructure and strength of porous spinel ceramics prepared by pore-forming in situ technique

Abstract: The porous spinel ceramics were prepared from magnesite and bauxite by the pore-forming in situ technique. The characterization of porous spinel ceramics was determined by X-ray diffractometer (XRD), scanning electron microscopy(SEM), mercury porosimetry measurement etc and the effects of particle size on microstructure and strength were investigated. It was found that particle size affects strongly on the microstructure and strength. With decreasing particle size, the pore size distribution occurs from multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…In this context, Archimedes' principle have been exploited widely and precisely in several explores to measure the density and porosity284041. Figure 6 depicts the changes in the trends in bulk density (i.e., mass per unit volume of a specimen), open porosity (i.e., ability to hold air or fluid by open voids present in a specimen), and close porosity (i.e., empty space without connecting via any open path or channel present inside a specimen) with the temperature at which the FBCBs were heat-treated (see Table S3 in Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, Archimedes' principle have been exploited widely and precisely in several explores to measure the density and porosity284041. Figure 6 depicts the changes in the trends in bulk density (i.e., mass per unit volume of a specimen), open porosity (i.e., ability to hold air or fluid by open voids present in a specimen), and close porosity (i.e., empty space without connecting via any open path or channel present inside a specimen) with the temperature at which the FBCBs were heat-treated (see Table S3 in Supplementary Information).…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, lightweight refractories, fabricated by a conventional powder-processing route with the incorporation of some pore-forming agents, have a pore structure with large pore size and inhomogeneous pore size distribution, and then have low strengths and low thermal-shock resistances, which limited the application of traditionally lightweight refractories for working lining of high-temperature furnaces. 2 Cordierite(2MgO•2Al 2 O 3 •5SiO 2 ) possesses a low thermalexpansion coefficient, an excellent thermal-shock resistance and chemical stability at elevated temperatures, and then the porous cordierite ceramics have attracted more attention. [3][4][5][6] However, the porous cordierite ceramics are not suitable for the working lining of furnaces, because (1) the homogeneous microstructure of porous ceramics is harmful to the thermal-shock resistance; (2) the mechanical properties of cordierite material are poor.…”
Section: Introductionmentioning
confidence: 99%
“…25 Yan et al reported fabrication of porous cordierite with interconnected pores through an in-situ technique, and the permeability of sample with a porosity of 40.3% was 2.31 x 10 -12 m 2 . 26 A comparison of permeability of samples having above mentioned two types of pore structures with almost similar porosity shows that those with interconnected pores have relatively higher gas permeability. Thus, porous ceramics with interconnected pores and adequate strength can be preferred for filter application.…”
Section: Accepted Manuscriptmentioning
confidence: 99%